Durability test method and device, electronic equipment and readable storage medium
By obtaining the initial and target working conditions test data of the electrolytic cell, combining the power supply operation data to simulate the real working conditions, and evaluating the durability of the catalyst, the problem of inaccurate durability testing of electrolytic catalysts in the prior art is solved, and the reliability of the test is improved sex.
Patent Information
- Application Number
- CN202411228772.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art cannot accurately evaluate the durability of electrolytic catalysts, resulting in inaccurate monitoring of the electrolytic process.
By obtaining the first test data of the electrolytic cell to be tested and the second test data after the target working condition test, the durability of the catalyst is calculated, and the operation data of the power supply is used to simulate the real working condition, including the start-stop working condition and the variable load working condition. Test to obtain the voltage change rate, internal resistance change rate and charge transfer impedance change rate.
It improves the accuracy of catalyst durability testing, makes the test results closer to real usage scenarios, and improves the reliability of the test.
Smart Images

Figure CN119199003A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrolysis technology, and in particular to a durability testing method, device, electronic device and readable storage medium. Background Art
[0002] An electrolytic catalyst is a chemical substance or compound that can accelerate the electrolysis reaction. It can provide an alternative reaction path, thereby reducing the activation energy of the reaction, allowing the chemical reaction in the electrolyte to proceed under lower energy and milder conditions. However, the catalytic effect of the catalyst will decrease during the electrolysis process, causing the electrolysis rate to decrease. Therefore, researchers need to evaluate the durability of the catalyst in order to accurately monitor the electrolysis process. However, the accuracy of the durability test of the catalyst in the prior art can no longer meet people's needs. Summary of the invention
[0003] The embodiments of the present application provide a durability testing method, device, electronic device and readable storage medium, which can improve the accuracy of durability testing of catalysts.
[0004] In a first aspect, the present application provides a durability testing method for testing the durability of an electrolytic catalyst, the testing method comprising:
[0005] Acquiring first test data of an electrolytic cell to be tested; wherein a catalyst is provided in the electrolytic cell to be tested;
[0006] Performing a target operating condition test on the electrolytic cell to be tested according to the operating data of the power supply;
[0007] Acquire second test data after the electrolytic cell to be tested undergoes the target operating condition test;
[0008] The durability of the catalyst is obtained according to the first test data and the second test data.
[0009] In one embodiment, before performing a target operating condition test on the electrolytic cell to be tested according to the operating data of the power supply, the method further includes:
[0010] The current and voltage data of the output signal of the photovoltaic array under actual illumination are obtained as the operation data of the power supply.
[0011] In one embodiment, the target operating condition test of the electrolytic cell to be tested according to the operating data of the power supply includes:
[0012] Performing a start-stop operating condition test on the electrolytic cell to be tested according to the operating data of the power supply;
[0013] Performing a variable load condition test on the electrolytic cell to be tested according to the operating data of the power supply;
[0014] The obtaining of second test data after the electrolytic cell to be tested undergoes the target operating condition test comprises:
[0015] Acquire the start-stop test data of the electrolytic cell to be tested after the start-stop working condition test;
[0016] Obtain variable load test data after the electrolytic cell to be tested undergoes the variable load condition test.
[0017] In one embodiment, the start-stop condition test of the electrolytic cell to be tested according to the operating data of the power supply includes:
[0018] The electrolytic cell to be tested is powered according to the operating data of the power supply, so that the average current density of the electrolytic cell to be tested is switched between a first current density and a second current density; the first current density is 3000 A / m 2 Up to 5000A / m 2 , the second current density is 0A / m 2 .
[0019] In one embodiment, the waveform of the power supply signal of the electrolytic cell to be tested is a square wave, and the first current density is 3000A / m 2 Up to 5000A / m 2 , the second current density is 0A / m 2 .
[0020] In one embodiment, the test data includes at least one of a polarization curve within a preset current range, a voltage at a preset current density, an internal resistance and a charge transfer impedance within a preset voltage range and a preset frequency range.
[0021] In one embodiment, obtaining the durability of the catalyst according to the first test data and the second test data includes:
[0022] Acquire the voltage change rate at the same preset current density in the first test data and the second test data;
[0023] Acquire the internal resistance change rate within the same preset voltage range and the same preset frequency range in the first test data and the second test data;
[0024] Acquire the charge transfer impedance change rate within the same preset voltage range and the same preset frequency range in the first test data and the second test data;
[0025] The durability of the catalyst is obtained according to the voltage change rate, the internal resistance change rate, and the charge transfer impedance change rate.
[0026] In a second aspect, the present application provides a durability testing device, comprising:
[0027] A first test module is used to obtain first test data of an electrolytic cell to be tested; the electrolytic cell to be tested is provided with a catalyst;
[0028] A working condition test module, used for performing a target working condition test on the electrolytic cell to be tested according to the operating data of the power supply;
[0029] A second test module, used for obtaining second test data of the electrolytic cell to be tested after the target operating condition test is performed;
[0030] A durability acquisition module is used to acquire the durability of the catalyst according to the first test data and the second test data.
[0031] In a third aspect, the present application provides an electronic device, including a memory and a processor, wherein the memory stores a computer program, and when the computer program is executed by the processor, the processor executes the steps of the above method.
[0032] In a fourth aspect, the present application provides a computer-readable storage medium having a computer program stored thereon, wherein the computer program implements the steps of the above method when executed by a processor.
[0033] In a fifth aspect, the present application provides a computer program product, including a computer program, which implements the steps of the above method when executed by a processor.
[0034] The above-mentioned durability test method, device, electronic device and readable storage medium can obtain the first test data and the second test data before and after the target working condition test of the electrolyzer to be tested, respectively, to learn the performance changes of the catalyst in the electrolyzer to be tested during the target working condition test, and then obtain the durability of the catalyst. It can be understood that the smaller the change in the performance of the catalyst during the target working condition test, the better the durability of the catalyst, and vice versa. Moreover, by determining the specific power supply parameters in the target working condition test based on the operating data of the power supply, the situation of the electrolyzer to be tested in the actual working condition can be simulated, so that the durability test results are closer to the actual usage scenario, greatly improving the reliability of the durability test. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 One of the flow charts of the durability testing method of one embodiment;
[0037] Figure 2 This is a second flow chart of a durability testing method according to an embodiment;
[0038] Figure 3 A current density diagram of a start-stop condition test in one embodiment;
[0039] Figure 4 An input current and input voltage diagram of a variable load condition test in one embodiment;
[0040] Figure 5 A sub-flow chart of obtaining durability of a catalyst according to first test data and second test data in one embodiment;
[0041] Figure 6 is a schematic structural diagram of a durability testing device according to an embodiment;
[0042] Figure 7 The figure is a diagram showing the internal structure of an electronic device according to an embodiment. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0044] The present application provides a durability test method for testing the durability of electrolytic catalysts, which can be specifically used to test the durability of catalysts in hydrogen production scenarios using alkaline water electrolysis. In the process of hydrogen production using alkaline water electrolysis, the catalyst not only needs to have high activity and high efficiency, but also must maintain long-term stability to meet the needs of industrial applications. Therefore, the present application provides a durability test method that can accurately evaluate the durability of catalysts in hydrogen production scenarios using alkaline water electrolysis.
[0045] Figure 1 This is a flowchart of a durability testing method according to an embodiment of the present invention. Figure 1 , the durability testing method includes steps 102 to 108.
[0046] Step 102, obtaining first test data of the electrolytic cell to be tested.
[0047] The first test data is the data obtained by installing the assembled electrolytic cell to be tested on the test bench and connecting the pipelines for the first test. Therefore, the first test data can be called the initial test data. The electrolyte in the electrolytic cell to be tested can be a KOH solution with a temperature of 80°C and a concentration of 30%, and a flow rate of 0.4m 3 The first test data may include data related to electrical performance, and may also include gas production data of the electrolytic cell to be tested. The data related to electrical performance include but are not limited to resistance data, voltage and current characteristic data, and the like.
[0048] Specifically, the electrolytic cell to be tested is composed of a cathode, an anode and a diaphragm. Among them, the diameter of the cathode is 10 cm and can be coated with a catalyst. The type of catalyst can be but is not limited to a noble metal catalyst, a transition metal catalyst and a carbon-based catalyst. The transition metal catalyst includes a nickel-based catalyst, such as Raney nickel. Raney nickel is a solid heterogeneous catalyst composed of fine nickel-aluminum alloy grains with a porous structure. From a microscopic point of view, each tiny particle of Raney nickel is a three-dimensional porous structure, which greatly increases its surface area and thus has a high catalytic activity. The anode can be but is not limited to a nickel wire mesh anode, which is a mesh electrode made of nickel. Nickel has excellent corrosion resistance and electrical conductivity, so that the nickel wire mesh anode performs well in electrolysis applications. The diaphragm part can be but is not limited to a polyphenylene sulfide (PPS) fiber diaphragm, a polyetheretherketone (PEEK) diaphragm, a polysulfone (PSF) diaphragm, a Zirfon diaphragm, etc. The PPS diaphragm has excellent thermal stability, chemical stability, flame retardancy and electrical insulation. It has high porosity, large specific surface area, easy functional modification, good structural controllability, and can well meet the performance requirements of the diaphragm for the electrolyzer to be tested for hydrogen production.
[0049] Step 104, performing a target operating condition test on the electrolytic cell to be tested according to the operating data of the power supply.
[0050] Among them, the power supply is used to power the electrolyzer to be tested in the actual use scenario. Specifically, the power supply can be a power grid, or it can be a power generation system that can convert clean energy into electrical energy, such as a photovoltaic power generation system, a hydropower generation system, a wind power generation system, etc. It is understandable that the output power of the power grid may fluctuate to a certain extent due to the interference of the power supply line, load fluctuations, etc. Affected by weather conditions, the fluctuation of the output power of the power generation system used to convert clean energy into electrical energy will be greater, and when the input power is lower than the lower limit of the electrolyzer load, the electrolyzer will be shut down. In the related art, a relatively stable power supply signal is usually used to power the electrolyzer to be tested, which results in the test results being unable to truly reflect the aging of the electrolyzer to be tested in the actual use scenario. Therefore, the present embodiment obtains and tests based on the operating data of the power supply, which can effectively improve the authenticity of the results of the durability test.
[0051] Furthermore, the operating data may include voltage data and current data at all times of the day throughout the year. Taking the photovoltaic power generation system as an example, it is understandable that the radiation conditions of the sun are different throughout the year. For example, the solar energy in summer is significantly stronger than the solar energy in winter. The radiation conditions of the sun in the same day are also different. For example, the solar energy during the day is significantly stronger than the solar energy at night. Therefore, obtaining voltage data and current data at all times of the day throughout the year can provide complete data support for the target operating condition test. Further, the target operating condition test items can be multiple, and according to the operating data of the photovoltaic power generation system, power supply signals of different voltages and currents are provided to the electrolyzer to be tested under different test items, so as to achieve a comprehensive and accurate operating condition test of the electrolyzer to be tested.
[0052] Step 106, obtaining second test data after the electrolytic cell to be tested is tested under target operating conditions.
[0053] After executing the target operating condition test, the state of the catalyst will change, and the operation of the electrolyzer to be tested will change. Specifically, when the input power of the electrolyzer to be tested is lower than the lower limit of the electrolyzer load, the electrolyzer will be shut down to generate a reverse current, causing the cathode catalyst to corrode and causing the catalyst to fall off. When the input power of the electrolyzer to be tested fluctuates frequently within a certain range, the electrolysis current of the electrolyzer to be tested will fluctuate, causing the surface of the catalyst particles to repeatedly transform between the metallic state and the oxidized state, which will cause the catalyst to fall off from the surface of the electrode, thereby reducing the life of the catalyst. Therefore, the second test data can be obtained, and the first test data and the second test data can be compared to characterize the durability of the catalyst by the difference between the two test data. Among them, the test items of the second test data and the first test data can be the same, and are also data related to electrical performance, such as but not limited to resistance data, voltage and current characteristic data, etc. It can be understood that in some embodiments, the test items in the second test data may also be different from the first test data, which is not limited here.
[0054] Step 108 , obtaining durability of the catalyst according to the first test data and the second test data.
[0055] In the embodiment of the application, by respectively obtaining the first test data and the second test data before and after the target working condition test of the electrolyzer to be tested, the performance change of the catalyst in the electrolyzer to be tested during the target working condition test can be learned, and then the durability of the catalyst can be obtained. It can be understood that the smaller the change in the performance of the catalyst during the target working condition test, the better the durability of the catalyst, and vice versa. Moreover, by determining the specific power supply parameters in the target working condition test based on the operating data of the power supply, the situation of the electrolyzer to be tested in the actual working condition can be simulated, so that the durability test results are closer to the actual usage scenario, greatly improving the reliability of the durability test.
[0056] In one of the embodiments, before the target operating condition test is performed on the electrolyzer to be tested according to the operating data of the power supply, the following steps are also included: obtaining the current and voltage data of the output signal of the photovoltaic array under actual illumination as the operating data of the power supply. Among them, the installed capacity of the photovoltaic array can be determined according to the actual use scenario of the electrolyzer to be tested, for example, it can be 10kW. That is, the photovoltaic array includes about 40 photovoltaic modules, and the rated power of each photovoltaic module is about 250W. Specifically, the current and voltage data can be imported into the power supply system of the electrolyzer to be tested. When performing the durability test, the power supply system directly calls the imported current and voltage data to perform the target operating condition test on the electrolyzer to be tested.
[0057] Figure 2 This is a second flow chart of a durability testing method according to an embodiment, referring to Figure 2 In one embodiment, the durability test method includes steps 202 to 212. The step of performing a target operating condition test on the electrolytic cell to be tested according to the operating data of the power supply includes steps 204 and 208, and the step of obtaining second test data after the electrolytic cell to be tested is tested under the target operating condition test includes steps 206 and 210. Steps 202 and 212 can refer to the above embodiments and will not be repeated here.
[0058] Step 202, obtaining first test data of the electrolytic cell to be tested.
[0059] Step 204, performing a start-stop condition test on the electrolytic cell to be tested according to the operating data of the power supply.
[0060] Among them, the start-stop condition test is an experimental method for evaluating the performance and durability of the electrolyzer to be tested during the startup and shutdown process. In the start-stop condition test, the electrolyzer to be tested needs to undergo multiple startup and shutdown operations, which will damage the catalyst and affect the overall performance of the electrolyzer to be tested. Therefore, the start-stop condition test can accurately reflect the impact of the startup and shutdown operations on the life of the catalyst. Exemplarily, the step is to perform a start-stop condition test on the electrolyzer to be tested according to the operating data of the power supply, including the following steps: powering the electrolyzer to be tested according to the operating data of the power supply, so that the average current density of the electrolyzer to be tested is switched between the first current density and the second current density. Among them, the first current density is greater than the second current density. The first current density can be understood as the average current density when the electrolyzer to be tested is in a startup state, and the second current density can be understood as the average current density when the electrolyzer to be tested is in a shutdown or approximately shutdown state. Optionally, the first current density can be the average current density of the electrolyzer to be tested when the power supply is powered with an average output power.
[0061] Furthermore, the waveform of the power supply signal of the electrolytic cell to be tested is a square wave, and the first current density is 3000A / m 2 Up to 5000A / m 2 , the second current density is 0A / m 2 , the electrolytic cell is in shutdown state at the second current density, so that the electrolytic cell to be tested generates a reverse current at the second current density, causing the cathode catalyst to corrode. Figure 3 , the first current density is 4000A / m 2 , the second current density is 0A / m 2 By repeatedly performing start-stop tests, the working condition of the electrolytic cell generating reverse current is simulated. Therefore, by reasonably setting the range of the first current density and the second current density and the start-stop time, the electrolytic cell can generate a larger reverse current and the catalyst can have enough time to be corroded by the reverse current, so as to test the effect of the reverse current generated by the start-stop condition on the catalyst performance.
[0062] Furthermore, each start-stop cycle of the catalyst durability test may last from 30 minutes to 70 minutes, for example, 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, etc. Taking a start-stop cycle lasting 45 minutes as an example, continue to refer to Figure 3 , the electrolytic cell to be tested can be maintained at the first current density for 30 minutes, then switched to the second current density, and then maintained at the second current density for 15 minutes, thereby completing a start-stop cycle. The number of starts and stops in the start-stop condition test can be 1000 times, 2000 times, 5000 times, etc., which is not limited here.
[0063] Step 206, obtaining the start-stop test data of the electrolytic cell to be tested after the start-stop operating condition test.
[0064] Step 208, performing a variable load condition test on the electrolytic cell to be tested according to the operating data of the power supply.
[0065] Among them, the variable load condition test is an experimental method to simulate and evaluate the performance and stability of the electrolytic cell to be tested under different load conditions. The variable load condition test includes but is not limited to rapidly changing current density cycles, long-term constant current or constant voltage operation, and emergency response tests under extreme conditions. Specifically, the variable load condition test may include multiple test cycles, and the current and voltage changes in each test cycle are consistent with the current and voltage output by the 10KW photovoltaic array under actual illumination. The duration of a test cycle can be 4000s, 8000s, 15000s, etc., and the number of cycles of the variable load condition test can be 1000 times, 2000 times, 5000 times, etc., which are not limited here.
[0066] Take a test cycle of 8000s as an example. Figure 4 In a test cycle, the input current of the electrolyzer to be tested mostly fluctuates in the range of 5A to 10A, and the input voltage mostly fluctuates in the range of 300V to 400V. Such frequent fluctuations will cause the catalyst to repeatedly switch between the metallic state and the oxidized state, resulting in the catalyst falling off. At the same time, in the time range of 2000s to 2500s, there is a large input voltage of about 800V, which will cause the input power to increase sharply, causing the catalyst to be impacted by a large current in a short time, resulting in the catalyst falling off. Therefore, by selecting an appropriate period of power supply operation data, the catalyst can be better tested under a wide range of power fluctuation conditions, thereby improving the effectiveness of the variable load condition test.
[0067] Step 210, obtaining the variable load test data after the variable load condition test of the electrolytic cell to be tested.
[0068] Step 212, obtaining the durability of the catalyst according to the first test data, the start-stop test data and the variable load test data.
[0069] In the embodiments of the application, the start-stop condition test can be used to obtain the impact of frequent start-stop operations on the catalyst, while the variable load condition test can be used to obtain the impact of the fluctuating output of the photovoltaic array on the catalyst. Therefore, by combining the two condition test methods, a comprehensive evaluation of the catalyst durability can be performed. Moreover, after each condition test, the start-stop test data and the variable load test data are obtained respectively, and the degree of influence of different condition tests on the catalyst can be compared, thereby providing a more detailed durability analysis result. It should be noted that in Figure 2In the embodiment shown, the start-stop condition test is performed first and then the variable load condition test is performed, but in some embodiments, the variable load condition test may be performed first and then the start-stop condition test, which is not limited here.
[0070] In one embodiment, the test data includes at least one of a polarization curve within a preset current range, a voltage at a preset current density, an internal resistance and a charge transfer impedance within a preset voltage range and a preset frequency range.
[0071] Among them, the polarization curve within the preset current range can be obtained by constant potential method, which includes static method and dynamic method. The static method refers to keeping the electrode potential constant at different values and measuring the corresponding stable current value, so as to obtain a complete polarization curve point by point. The dynamic method refers to controlling the electrode potential to change (scan) continuously at a slower speed and measuring the instantaneous current value at the corresponding potential. The voltage at the preset current density can be obtained by constant current method, which refers to controlling the current density on the electrode to be constant at different values in turn and measuring the corresponding stable electrode potential value at the same time. The internal resistance within the preset voltage range and the preset frequency range can be obtained by electrochemical impedance spectroscopy (EIS). Specifically, the required alternating current signal can be provided to the electrolytic cell to be tested by the EIS instrument, and the alternating current signal is set to an appropriate preset frequency range and a preset voltage range of the alternating current signal, so as to accurately measure the current and voltage response of the electrolytic cell to be tested. The internal resistance within the preset voltage range and the preset frequency range can be obtained based on the current and voltage response. The charge transfer impedance within the preset voltage range and the preset frequency range can be obtained by AC impedance testing. Specifically, the test system of the AC impedance test includes an electrochemical workstation, an electrolytic current source, a multimeter and a spectrum analyzer. A subtle AC signal, such as a small-amplitude sinusoidal AC signal, is applied to the electrolytic cell to be tested through the electrolytic current source, and the impedance of the system is measured by the electrochemical workstation, so that the impedance information at different frequencies can be analyzed to reveal the various electrode reactions and electrolyte transfer processes in the electrolytic cell to be tested.
[0072] In the embodiments of the application, by evaluating the status of the electrolytic cell before and after the target operating condition test from different dimensions, the changes in the catalyst can be more accurately obtained, and then the durability of the catalyst can be obtained.
[0073] Figure 5 A sub-flow chart of obtaining the durability of a catalyst according to first test data and second test data according to an embodiment, referring to Figure 5 In one embodiment, the above steps include steps 502 to 508.
[0074] Step 502: Obtain the voltage change rate at the same preset current density in the first test data and the second test data.
[0075] Step 504 , obtaining the internal resistance change rate within the same preset voltage range and preset frequency range in the first test data and the second test data.
[0076] Step 506 : Obtain the charge transfer impedance change rate within the same preset voltage range and preset frequency range in the first test data and the second test data.
[0077] It should be noted that, when the start-stop condition test is performed first and the variable load condition test is performed later, the first test data and the start-stop test data, the start-stop test data and the variable load test data, and the first test data and the variable load test data can be compared in pairs. For example, the voltage change rate at the same preset current density in the first test data and the start-stop test data, the voltage change rate at the same preset current density in the start-stop test data and the variable load test data, and the voltage change rate at the same preset current density in the first test data and the variable load test data can be obtained respectively.
[0078] Specifically, Table 1 is a comparison table of the voltage change rate, internal resistance change rate and charge transfer impedance change rate of an embodiment. Referring to Table 1, the voltage change rate reflects the stability of the catalyst during the electrochemical reaction. A stable voltage means that the catalyst can continuously and effectively promote the reaction, while a voltage fluctuation may indicate that the active surface of the catalyst has degraded. Therefore, at the same current density, if the voltage change rate of the electrolyzer to be tested is small, it means that the catalyst has good durability. Charge transfer impedance (Rct) is used to describe the ease of charge transfer on the interface between the electrode and the electrolyte, while internal resistance refers to the ohmic internal resistance of the electrolyzer. The detached catalyst will adhere to the diaphragm, block the diaphragm pores, affect the transmission of the electrolyte, and increase the resistance. Internal resistance not only affects the hydrogen production efficiency and energy consumption of the electrolyzer, but is also affected by temperature, inter-electrode spacing, etc. Charge transfer impedance focuses more on describing the kinetic process on a specific electrochemical reaction interface. It can be understood that the lower the charge transfer impedance and internal resistance, the better the performance of the electrolyzer to be tested, and the better the performance of the corresponding catalyst. Therefore, if the rate of change of the internal resistance and charge transfer impedance is small, it indicates that the catalyst has good durability.
[0079] Table 1 Comparison table of voltage change rate, internal resistance change rate and charge transfer impedance change rate
[0080]
[0081] Step 508 , obtaining the durability of the catalyst according to the voltage change rate, the internal resistance change rate and the charge transfer impedance change rate.
[0082] Specifically, the voltage change rate, internal resistance change rate and charge transfer impedance change rate can be weighted averaged to obtain comprehensive durability data. In the embodiment of the application, the performance degradation of the electrolytic cell to be tested is evaluated based on the change rate, which can achieve a quantitative evaluation of the durability of the catalyst, so that other model building operations can be performed based on the quantitative data to conduct a more in-depth analysis and prediction of the durability of the catalyst.
[0083] It should be understood that, although the steps in the flowcharts involved in the above embodiments are displayed in sequence according to the indication of the arrows, these steps are not necessarily executed in sequence according to the order indicated by the arrows. Unless there is a clear explanation in this article, the execution of these steps is not strictly limited in order, and these steps can be executed in other orders. Moreover, at least a part of the steps in the flowcharts involved in the above embodiments may include multiple steps or multiple stages, and these steps or stages are not necessarily executed at the same time, but can be executed at different times, and the execution order of these steps or stages is not necessarily carried out in sequence, but can be executed in turn or alternately with other steps or at least a part of the steps or stages in other steps.
[0084] Based on the same inventive concept, the embodiment of the present application also provides a durability testing device for implementing the durability testing method involved above. The implementation scheme for solving the problem provided by the device is similar to the implementation scheme recorded in the above method, so the specific definition of one or more durability testing device embodiments provided below can refer to the definition of the durability testing method above, and will not be repeated here.
[0085] The embodiment of the present application also provides a durability testing device, Figure 6 is a schematic diagram of the structure of a durability testing device according to an embodiment, referring to Figure 6, in one embodiment, the durability testing device includes a first data collection module, a working condition test module, a second data collection module and a durability acquisition module. Among them, the first data collection module is used to obtain the first test data of the electrolytic cell to be tested; a catalyst is provided in the electrolytic cell to be tested. The working condition test module is used to perform a target working condition test on the electrolytic cell to be tested according to the operating data of the power supply. The second data collection module is used to obtain the second test data after the electrolytic cell to be tested is tested under the target working condition test. The durability acquisition module is used to obtain the durability of the catalyst according to the first test data and the second test data. In the embodiment of the application, by respectively obtaining the first test data and the second test data before and after the electrolytic cell to be tested is tested under the target working condition test, the performance change of the catalyst in the electrolytic cell to be tested during the target working condition test can be learned, and then the durability of the catalyst can be obtained. It can be understood that the smaller the change in the performance of the catalyst during the target working condition test, the better the durability of the catalyst, and vice versa. Moreover, by determining the specific power supply parameters in the target operating condition test based on the operating data of the power supply, the situation of the electrolyzer to be tested in the actual operating conditions can be simulated, so that the durability test results are closer to the actual usage scenarios, greatly improving the reliability of the durability test.
[0086] In one of the embodiments, the durability testing device further includes an operation data acquisition module for acquiring current and voltage data of an output signal of the photovoltaic array under actual illumination as operation data of the power supply.
[0087] In one embodiment, the operating condition test module includes a start-stop operating condition test unit and a variable load operating condition test unit. The start-stop operating condition test unit is used to perform a start-stop operating condition test on the electrolytic cell to be tested according to the operating data of the power supply, and the variable load operating condition test unit is used to perform a variable load operating condition test on the electrolytic cell to be tested according to the operating data of the power supply. The second data collection module includes a start-stop data collection unit and a variable load data collection unit. The start-stop data collection unit is used to obtain the start-stop test data of the electrolytic cell to be tested after the start-stop operating condition test, and the variable load data collection unit is used to obtain the variable load test data of the electrolytic cell to be tested after the variable load operating condition test.
[0088] In one embodiment, the start-stop condition test unit is used to supply power to the electrolytic cell to be tested according to the operating data of the power supply, so that the average current density of the electrolytic cell to be tested is switched between a first current density and a second current density; the first current density is 3000A / m 2 Up to 5000A / m 2 , the second current density is 0A / m 2 .
[0089] In one embodiment, the waveform of the power supply signal of the electrolytic cell to be tested is a square wave, and the first current density is 3000A / m 2Up to 5000A / m 2 , the second current density is 0A / m 2 .
[0090] In one embodiment, the test data includes at least one of a polarization curve within a preset current range, a voltage at a preset current density, an internal resistance and a charge transfer impedance within a preset voltage range and a preset frequency range.
[0091] In one of the embodiments, the durability acquisition module is used to obtain the voltage change rate at the same preset current density in the first test data and the second test data; obtain the internal resistance change rate within the same preset voltage range and preset frequency range in the first test data and the second test data; obtain the charge transfer impedance change rate within the same preset voltage range and preset frequency range in the first test data and the second test data; and obtain durability based on the voltage change rate, the internal resistance change rate and the charge transfer impedance change rate.
[0092] Each module in the durability test device can be implemented in whole or in part by software, hardware, or a combination thereof. Each module can be embedded in or independent of a processor in an electronic device in the form of hardware, or can be stored in a memory in an electronic device in the form of software, so that the processor can call and execute operations corresponding to each module.
[0093] In one embodiment, an electronic device is provided, which may be a terminal. Figure 7 FIG. 1 is an internal structure diagram of an electronic device according to an embodiment of the present invention. Figure 7, the electronic device includes a processor, a memory, an input / output interface, a communication interface, a display unit and an input device. The processor, the memory and the input / output interface are connected through a system bus, and the communication interface, the display unit and the input device are connected to the system bus through the input / output interface. The processor of the electronic device is used to provide computing and control capabilities. The memory of the electronic device includes a non-volatile storage medium and an internal memory. The non-volatile storage medium stores an operating system and a computer program. The internal memory provides an environment for the operation of the operating system and the computer program in the non-volatile storage medium. The input / output interface of the electronic device is used to exchange information between the processor and an external device. The communication interface of the electronic device is used to communicate with an external terminal in a wired or wireless manner, and the wireless manner can be implemented through WIFI, a mobile cellular network, NFC (near field communication) or other technologies. When the computer program is executed by the processor, a durability test method is implemented. The display unit of the electronic device is used to form a visually visible picture, which can be a display screen, a projection device or a virtual reality imaging device. The display screen can be a liquid crystal display screen or an electronic ink display screen, and the input device of the electronic device can be a touch layer covering the display screen, or a button, trackball or touchpad set on the electronic device casing, or an external keyboard, touchpad or mouse.
[0094] Those skilled in the art will understand that Figure 7 The structure shown in the figure is only a block diagram of a part of the structure related to the present application scheme, and does not constitute a limitation on the electronic device to which the present application scheme is applied. The specific electronic device may include Figure 7 More or fewer components may be shown, or certain components may be combined, or may have a different arrangement of components.
[0095] The embodiment of the present application also provides a computer-readable storage medium, which is one or more non-volatile computer-readable storage media containing computer-executable instructions, and when the computer-executable instructions are executed by one or more processors, the processors execute the steps of the durability testing method.
[0096] The embodiment of the present application also provides a computer program product including instructions, which, when executed on a computer, enables the computer to execute the durability testing method.
[0097] Those skilled in the art can understand that all or part of the processes in the above-mentioned embodiments can be completed by instructing the relevant hardware through a computer program, and the computer program can be stored in a non-volatile computer-readable storage medium. When the computer program is executed, it can include the processes of the embodiments of the above-mentioned methods. Among them, any reference to the memory, database or other medium used in the embodiments provided in this application can include at least one of non-volatile and volatile memory. Non-volatile memory can include read-only memory (ROM), magnetic tape, floppy disk, flash memory, optical memory, high-density embedded non-volatile memory, resistive random access memory (ReRAM), magnetoresistive random access memory (MRAM), ferroelectric random access memory (FRAM), phase change memory (PCM), graphene memory, etc. Volatile memory can include random access memory (RAM) or external cache memory, etc. As an illustration and not limitation, RAM can be in various forms, such as static random access memory (SRAM) or dynamic random access memory (DRAM). The database involved in each embodiment provided in this application may include at least one of a relational database and a non-relational database. Non-relational databases may include distributed databases based on blockchains, etc., but are not limited to this. The processor involved in each embodiment provided in this application may be a general-purpose processor, a central processing unit, a graphics processor, a digital signal processor, a programmable logic device, a data processing logic device based on quantum computing, etc., but are not limited to this.
[0098] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0099] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A durability testing method, characterized in that: Used to test the durability of electrolytic catalysts, the test method includes: Acquiring first test data of an electrolytic cell to be tested; wherein a catalyst is provided in the electrolytic cell to be tested; Performing a target operating condition test on the electrolytic cell to be tested according to the operating data of the power supply; Acquire second test data after the electrolytic cell to be tested undergoes the target operating condition test; The durability of the catalyst is obtained according to the first test data and the second test data.
2. The durability testing method according to claim 1, characterized in that: Before the target operating condition test is performed on the electrolytic cell to be tested according to the operating data of the power supply, the method further includes: The current and voltage data of the output signal of the photovoltaic array under actual illumination are obtained as the operation data of the power supply.
3. The durability testing method according to claim 1, characterized in that: The step of performing a target operating condition test on the electrolytic cell to be tested according to the operating data of the power supply comprises: Performing a start-stop operating condition test on the electrolytic cell to be tested according to the operating data of the power supply; Performing a variable load condition test on the electrolytic cell to be tested according to the operating data of the power supply; The obtaining of second test data after the electrolytic cell to be tested undergoes the target operating condition test comprises: Acquire the start-stop test data of the electrolytic cell to be tested after the start-stop working condition test; Obtain variable load test data after the electrolytic cell to be tested undergoes the variable load condition test.
4. The durability testing method according to claim 3, characterized in that: The starting and stopping operating condition test of the electrolytic cell to be tested is performed according to the operating data of the power supply, comprising: The electrolytic cell to be tested is powered according to the operating data of the power supply, so that the average current density of the electrolytic cell to be tested is switched between a first current density and a second current density; the first current density is 3000 A / m 2 Up to 5000A / m 2 , the second current density is 0A / m 2 .
5. The durability testing method according to claim 4, characterized in that: The waveform of the power supply signal of the electrolytic cell to be tested is a square wave, and the first current density is 3000A / m 2 Up to 5000A / m 2 , the second current density is 0A / m 2 .
6. The durability testing method according to claim 1, characterized in that: The test data includes at least one of a polarization curve within a preset current range, a voltage at a preset current density, an internal resistance and a charge transfer impedance within a preset voltage range and a preset frequency range.
7. The durability testing method according to claim 6, characterized in that: The obtaining the durability of the catalyst according to the first test data and the second test data includes: Acquire the voltage change rate at the same preset current density in the first test data and the second test data; Acquire the internal resistance change rate within the same preset voltage range and the same preset frequency range in the first test data and the second test data; Acquire the charge transfer impedance change rate within the same preset voltage range and the same preset frequency range in the first test data and the second test data; The durability of the catalyst is obtained according to the voltage change rate, the internal resistance change rate, and the charge transfer impedance change rate.
8. A durability testing device, characterized in that: include: A first test module, used to obtain first test data of the electrolytic cell to be tested; The electrolytic cell to be tested is provided with a catalyst; A working condition test module, used for performing a target working condition test on the electrolytic cell to be tested according to the operating data of the power supply; A second test module, used for obtaining second test data of the electrolytic cell to be tested after the target operating condition test is performed; A durability acquisition module is used to acquire the durability of the catalyst according to the first test data and the second test data.
9. An electronic device comprising a memory and a processor, wherein a computer program is stored in the memory, wherein: When the computer program is executed by the processor, the processor is caused to perform the steps of the method according to any one of claims 1 to 7.
10. A computer-readable storage medium having a computer program stored thereon, characterized in that: When the computer program is executed by a processor, the steps of the method according to any one of claims 1 to 7 are implemented.
11. A computer program product, comprising a computer program, characterized in that When the computer program is executed by a processor, the steps of the method according to any one of claims 1 to 7 are implemented.
Citation Information
Cited By
Method for testing durability of anion exchange membrane electrolytic cell
CN120522258A
Aging test method of electric hydrogen production system for simulating fluctuation working condition of new energy microgrid
CN120761758A
An aging test method for an electric hydrogen production system simulating fluctuation conditions of a new energy microgrid
CN120761758B
Electrolytic bath testing method and device
CN121295250A
Adjustment capability information determination method and device, storage medium and electronic equipment
CN122533020A
